Evaluation of an Enzyme Immunoassay and TPPA for Detection of Antibodies Against Treponema Palladium - Maharjan, Anil; Karki, S.; Shrestha, S.; Rajkarnikar, M. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Screening treponemal antibodies; Treponema palladium; ELISA; TP-PA DOI: 10.3126/jnhrc.v5i2.2449 Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 1-4